Synthesis of nanometer-sized ceramic particles. - Chuah Abdullah, Luqman; Mirjalili, Fatemeh; Mohamad, Hasmaliza; Ahmadun, Fakhru'l-Razi; Awang Biak, Dayang Radiah (2010)

(untitled)
The present invention discloses a method to manufacture nano-sized α-Al2O3 powders having a particle size from about 15 nm to about 30 nm, whilst preventing excessive grain growth and aggregation of nanoparticles. In an aspect of the present invention, the particle size and shape of the nano α-Al2O3 powders can be controlled by using sodium dodecylbenzen sulfonate (SDBS) and sodium bis-2-ethylhexyl sulfosuccinate (Na(AOT)) as surfactant stabilizing agents. In another aspect, the size and shape of the nano α-Al2O3 powders can be controlled by forming aqueous solutions stirred for different periods of time, i.e 24, 36, 48 and 60 hours, at 60?C.